Smart work and efficiency at the work place - Hassan, Samah Abdel Geleel (AUC Knowledge Fountain, 2016)
This research is the first comparative study on Smart Work, specifically in academic institutions. The study uses the University of California, Berkeley as a benchmark to investigate the context and perspectives of smart work, and how best practices can be extended to AUC, as well other universities. Smart work proposes that when employees are able to tailor their working arrangements to fit personal commitments, they can create a motivated workforce, and produce the highest quality of work. Smart Work is not less beneficial for the academic institution, than it is for the employee. It helps achieve job satisfaction, in addition to institutional goals. Smart Work does not pose any conflict between personal wellbeing, and economic growth. Smart Work is based on three main factors. Policy making is essential for identifying the right framework that best suits employees’ needs and helps them achieve efficiency at the workplace. Secondly, implementation of policies is beneficial in many ways. It ensures that customer needs are met, encourages assessment and monitoring tools to warrant improved productivity. Finally, management support increases trust with the employer, since it eliminates inequality within the workforce. Support of the management is a clear sign that the university has the best interest of the employees in mind, through offering flexibility, benefits and professional development opportunities. This creates a strong sense of loyalty, and job satisfaction retention of the best caliber of employees. Empirical evidence on the various forms of smart work can be identified as: “providing employees with flexibility is associated with positive outcomes in terms of health and well-being, as well as positive institutional outcomes such as increased productivity, staff retention. Conversely, denying workers control over their work schedules results in negative well-being outcomes” (Tucker and Folkard, 2011, page 34).